Faktor - Faktor Yang Mempengaruhi Terjadinya Hiperbilirubinemia Pada Neonatus Di RS Budi Kemuliaan Periode Januari–Juli 2023 - Agustina Hermansyah, Herfiana; Sapriani, Irma; Yulika, Indah; Sunarti , Tri (Jurnal Ilmiah Kesehatan, 2024)
Hyperbilirubinaemia is one of the problems that often occur in neonates. Hyperbilirubinaemia is the number 5 cause of neonatal morbidity in Indonesia with a prevalence of 5.6% after respiratory distress, prematurity, sepsis, and hypothermia. The Neonatal Mortality Rate (NMR) in Indonesia in 2021 was 11.7 out of 1,000 live births. In the period 2021 to 2022 there was an increase in the incidence of hyperbilirubinemia at Budi Kemuliaan Hospital, namely in 2021 it was 15% of 3,566 live births, increasing the percentage to 16% of 3,145 live births in 2022. The purpose of this study was to determine whether there is an association between the factors of gestational age, birth weight, mode of delivery and nutritional intake with hyperbilirubinemia. The research method used case control design with consecutive sampling technique on secondary data from medical records. The subjects of this study were neonates born at Budi Kemuliaan Hospital who experienced hyperbilirubinemia in the period January-July 2023, in the case group as many as 78 and the control group as many as 78 with a total of 156 neonates. The results of this study showed that there was a significant association between nutritional intake and hyperbilirubinemia (P=0.000, OR=8.4, IK=3.983-17.920), while no significant association was found in gestational age, birth weight, and mode of delivery.